Pengaruh Asimetri Informasi, Financial Distress, dan Good Corporate Governance terhadap Manajemen Laba - Tifalia Izzati Yaumi Sabila; Endah Susilowati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to test and prove empirically the effect of information asymmetry, financial distress, managerial ownership, and audit committee on earnings management. The population used is all annual reports of infrastructure companies in the building construction sector listed on the Indonesia Stock Exchange for the period 2018-2022, with a total sample of 12 companies. The test method uses partial least square (PLS) which is processed with SmartPLS for Windows Version 3.0. The results showed that information asymmetry, financial distress, managerial ownership, and audit committee have a positive and significant effect on earnings management.